1981
DOI: 10.1002/1520-6807(198104)18:2<144::aid-pits2310180204>3.0.co;2-t
|View full text |Cite
|
Sign up to set email alerts
|

Cautions in interpreting WRAT standard scores as criterion measures of achievement in young children

Abstract: The present article calls into question the use of the WRAT as a criterion measure for determining ability/achievement discrepancies in young school-aged children. It is demonstrated that the use of regression equations to predict the expected achievement levels of five-and six-year-old children on the WRAT still does not rectify the difficulties in identifying underachievement for children in the lower primary grades. Implications for the early identification of specific learning disabilities are discussed.Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
1

Year Published

1983
1983
1985
1985

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 4 publications
0
4
1
Order By: Relevance
“…Snart et al claim that Silverstein (1978) found that WRAT scores were overestimated but in fact there seems to be, in most cases, little difference (0-8 points) between the standard scores that were calculated on the basis of the WRAT norms and those calculated norms from another sample. Contrary to the assertions of Snart et al, Grossman (1981) does not actually present any evidence that WRAT scores overestimate the performance of young children.…”
Section: Siegel Mcmaster Universitycontrasting
confidence: 82%
“…Snart et al claim that Silverstein (1978) found that WRAT scores were overestimated but in fact there seems to be, in most cases, little difference (0-8 points) between the standard scores that were calculated on the basis of the WRAT norms and those calculated norms from another sample. Contrary to the assertions of Snart et al, Grossman (1981) does not actually present any evidence that WRAT scores overestimate the performance of young children.…”
Section: Siegel Mcmaster Universitycontrasting
confidence: 82%
“…Obviously we are not the first to have concerns about the accuracy of the WRAT in reflecting the true academic or achievement levels of children and adults. However, despite an abundance of recent criticism by American psychologists and educators (Grossman, 1981;Salvia & Ysseldyke, 1978;Silverstein, 1978), the WRAT continues to be used in both the U.S. and Canada, perhaps because it can be administered and scored relatively easily and quickly, and perhaps because users lack an awareness of better alternatives and/or the serious problems which exist with the instrument. In Canadian populations, for whom the WRAT was never normed, the latter problems are further compounded, and we would therefore like to make some cautionary comments to WRAT users.…”
mentioning
confidence: 99%
“…Given the present data and an abundance of anecdotal evidence gleaned from conversations with elementary school teachers, we would suggest that both the 1976 and 1978 norms, for reading at least, consistently overestimate grade-level performance on word recognition by approximately 1 to 2 years, thus negating their utility either for pinpointing a disability or for suggesting appropriate instructional levels. Especially at younger ages the overestimation and variability of scores are even greater (Grossman, 1981). If the WRAT reading test is given on an individual basis, one could infer from the published norms that a child who is actually 1 or 2 years behind age-mates is functioning appropriately in reading, or conversely that a child who in fact is functioning in line with age-mates should be in an advanced reading program.…”
mentioning
confidence: 99%
See 2 more Smart Citations